Transformasi Pelayanan Publik: Strategi Menghadapi Era Society 5.0 - Irsad Munawir; Pandu Pamungkas (MAN 4 Kota Pekanbaru, 2026)
Rapidly developing digital technology has drastically changed human life, including the way public services are delivered. The concept of Society 5.0 has emerged as a new model that focuses on the use of technology for humans, with the aim of improving the welfare and quality of life of society. This article aims to comprehensively describe public services in the era of Society 5.0 through a literature study approach. The research method used is a literature study by reviewing scientific journals, academic books, and policy documents relevant to public services and Society 5.0. The results of the study show that public services in the era of Society 5.0 are characterized by the integration of advanced digital technologies such as artificial intelligence, big data, and the Internet of Things in the service process, as well as a shift in service orientation that is more focused on the needs and experiences of the community. Public services not only function as a mechanism for administrative fulfillment, but also as an instrument for creating sustainable public value. This article outlines a public service 5.0 model based on human-centred digital governance, hybrid governance services, and public complaints as evaluative indicators for creating sustainable public value.